P2 Levels of the novel peptide intermedin/adrenomedullin-2 in patients with pulmonary arterial hypertension. (May 2019) - Thomas, Gavin; Watson, Chris; McMechan, Stephen; Smyth, Anita; Bell, David; Harbinson, Mark T
Abstract : Background and aim: The novel peptide intermedin/adrenomedullin-2 (IMD) exhibits important vasodilator and anti-hypoxic effects in various circulatory disorders including hypertension and heart failure. IMD levels in patients with pulmonary arterial hypertension (PAH), a disorder characterised by local vasoconstriction and hypoxia, are unknown. The aim of the study therefore was to explore the relationship between serum levels of IMD and pathologically important echocardiographic and invasive haemodynamic measurements in patients with PAH. Methods: Blood was drawn from patients with PAH, separated, solid-phase extraction carried out, and IMD levels assayed by ELISA. Patients with PAH related to diagnostic classes 1, 4 and 5 were included. Age-matched patients without PAH served as controls. Standard echocardiography with additional assessment of the right ventricle and pulmonary pressures was carried out. Invasive right heart catheterisation was performed according to standardised protocols. The relationship between IMD and the echocardiographic and catheter variables was determined. Results: 21 individuals were recruited; eight patients with PAH and 13 control subjects. As expected, patients with PAH had worse NYHA class, reduced six minute walk distance and worse pulmonary function tests. Measures of right ventricular pressure and right atrial pressure were markedly abnormal and trans-pulmonary gradient and pulmonary vascular resistance were markedly elevated in patients with PAH. Echocardiography demonstrated the expected reduction in right ventricular performance. The overall levels of IMD in the peripheral blood were not significantly different between patients with PAH and controls (2.7+/-2.1 patients v 2.2+/-0.7 ng/ml; p=0.36). However relationships were noted between serum IMD levels and pathophysiological parameters of disease. There was a moderate to strong inverse relationship between central oxygen saturation and IMD levels (r=−0.78). IMD levels tended towards inverse relationships with right ventricular performance measured by RV TEI index (r=0.68), fractional area change (RV-FAC; r=−0.46), and right ventricular diastolic pressure (r=0.61). Conclusion: IMD is correlated with measures of oxygenation, right ventricular performance and pressure in patients with PAH. The lack of a major difference in peripheral blood level of IMD between PAH patients and control subjects indicates that a paracrine effect may be operative; further study of local IMD levels within the pulmonary circulation is warranted. This study was funded by the Heart Trust Fund and Southeastern Health and Social Care Trust Research Fellowship (awarded to G Thomas).